Inovasi Pembelajaran Berbasis Media TASAKU (Studi di Sekolah Dasar Negeri Mojorejo 01 Kota Batu, Jawa Timur) - Alifah Retno Wulan; Sugiarti Sugiarti; Nurina Manggiasih (Jurnal Manajemen Pendidikan Dasar, Menengah dan Tinggi [JMP-DMT], 2023)
Based on the results of observations and interviews, it was found that the problem was that students had difficulty in converting units of length cm and m. This is because learning activities have not used appropriate learning media, thus making students less enthusiastic. Students have not been able to understand the material to the fullest because the material is too abstract so that they have not reached learning mastery. For this reason, it is necessary to have teaching aids to make it easier for students to solve the problem of converting units of length cm and m. This study aims to improve student learning outcomes about unit length conversion material cm and m with Tasaku learning media in class IIIA SDN Mojorejo 01 Batu City. This type of research is Classroom Action Research (CAR), which consists of 2 cycles. Each cycle consists of 2 meetings. The data were obtained from the teacher's activities in teaching and student learning outcomes in working on the questions. The stages used in this study consisted of planning, implementing, observing, and reflecting. Data collection techniques used are observation, interviews, tests, and documentation. The results showed that there was a significant increase in student learning outcomes. The average student learning outcomes in pre-cycle was 61 with mastery learning of 39%, in cycle I the average score was 69 with learning mastery was 55%, and in cycle II the average score was 83 with learning completeness was 97%. Based on the results of this study, it can be concluded that student learning outcomes on unit length conversion material cm and m by using Tasaku learning media can be increased.